PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS NILAI-NILAI ISLAM PADA MATERI ARITMATIKA SOSIAL - Rahmawati, Arni; Rizki, Swaditya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The objective of this research and development is to develop teaching materials of mathematics on social arithmetic based on Islamic values that are feasible, practical, and effective. This research type is Research and Development (R&D). The model used in this research is consisting of 10 stages. The instruments of data collection used the questionnaires and evaluation questions. The questionnaires are consisting of design, material, and Islamic content. The result of the research is the average of validation percentage is 82,3%, so the teaching material is categorized as feasible. Based on the validation process showed that the teaching material that developed is included the feasible category, with an average percentage are 82.3%. While the results of small group trial showed that the responses of students in the pilot phase of small groups from 16 students are obtained Â 87.5%, and the result from the test is obtained the average more than 75% of the students who score more than the standard of 75.00. From the results of this research can be concluded that the teaching material of social arithmetic is feasible, practical, and effective.